Interfacial Cooperative Assembly of Surfactants and Opposite Wettability Nanoparticles Stabilizes Water-in-Oil Emulsions at High Temperature - Hu, Junjie (Langmuir : the ACS journal of surfaces and colloids, 2024)
Pickering emulsions have promising applications in the development of unconventional oil and gas resources. However, the high-temperature environment of the reservoir is not conducive to the stabilization of Pickering emulsions. In addition, the preparation of Pickering emulsions under low-energy emulsification and low-concentration emulsifier conditions is a difficult challenge. Here, we report a high-temperature resistant water-in-paraffin oil Pickering emulsion, which is synergistically stabilized by polyglycerol ester (PGE) and nanoparticles with opposite wettability (lipophilic silica and hydrophilic alumina). This emulsion can be prepared under mild stirring (500 rpm) conditions and can be stable at 140 °C for at least 30 days. The synergistic effects of surfactant, silicon nanoparticles (MSNPs) with different wettability, and alumina nanoparticles (AONPs) on the stability of both emulsions and water-oil interfacial membranes were investigated through bottle experiments, cryogenic scanning electron microscopy (cryo-SEM), optical microscopy, fluorescence microscopy, etc. The results showed that both hydrophobic MSNPs and hydrophilic AONPs are adsorbed together at the water-oil interface to stabilize the W/O emulsion, which can be prepared by 500 rpm stirring. The stability of emulsions strongly depends on the wettability of MSNPs, and the MSNP with moderate hydrophobicity (for example, aqueous phase contact angle of 136°) makes the emulsion exhibit the highest stability against aggregation and settling at elevated temperatures. The emulsion stabilization mechanism was revealed in terms of the adsorption capacity of the surfactant by MSNPs, the adsorption morphology and desorption energy of nanoparticles at the water-oil interface adsorption layer, and emulsion rheology. These findings demonstrate a novel and simple strategy to prepare Pickering W/O emulsions with high-temperature stability at low shear strength